2022
DOI: 10.22605/rrh7442
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using telephone interviews and internet-based message services during the COVID-19 pandemic in rural Sri Lanka: experiences of the Rajarata Pregnancy Cohort

Abstract: The COVID-19 pandemic has challenged population health researchers to use remote data collection methods to avoid faceto-face interaction. A proper assessment of the feasibility of these methods in low-resource settings is lacking. We share our experience from telephone interviews conducted among pregnant women in the Rajarata Pregnancy Cohort in Sri Lanka. Among 3374 participants, 3284 (98.4%) and 496 (14.7%) had mobile and fixed-access phones respectively. During interviews, 1576 (51.9%) of participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, further work is required to establish the viability of this program. Using a large-scale, population-based pregnancy cohort, Jayasinghe and colleagues [ 68 ] recruited 3374 first-trimester pregnant women registered with midwives at the field prenatal clinics to assess the feasibility and the coverage and feasibility of app-based interventions and generalizability of telephone interviews for psychological support during the pandemic. The study revealed that mHealth led to selection bias and that mHealth may not be the best strategy for interventions in this remote area.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further work is required to establish the viability of this program. Using a large-scale, population-based pregnancy cohort, Jayasinghe and colleagues [ 68 ] recruited 3374 first-trimester pregnant women registered with midwives at the field prenatal clinics to assess the feasibility and the coverage and feasibility of app-based interventions and generalizability of telephone interviews for psychological support during the pandemic. The study revealed that mHealth led to selection bias and that mHealth may not be the best strategy for interventions in this remote area.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of the synthesized studies demonstrate the similarities and differences between participant characteristics and intervention modalities used from prenatal through delivery and postpartum. For instance, there were considerable differences in study participants ages, with most studies using both the birth age of the mother and gestation age, while a few studies did not include age but referenced the age of participants as women of reproductive age [ 100 ] or pregnant women [ 68 , 101 , 103 , 109 , 124 , 125 ], or women with children under 2 years old [ 105 , 113 , 126 ]. Likewise, although two studies conducted in the US used a similar mHealth intervention delivered via Headspace™ app and with patients with moderate-to-moderately-severe depression as well as duration (use of app for 10 to 20 minutes a day for 6 weeks), they focused on different stages of pregnancy, gestation age and patient birth ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the permission of pregnant women during recruitment of the RaPCo, we collected their telephone numbers to contact them to share the investigation results and follow-up data collection. We held a telephone interview using a pretested interviewer guide with close-ended questions and collected details on the routine utilisation of antenatal/postnatal health services and household financial information during the pandemic 33. Data collection was based on five major categories: (1) whether income was affected during the outbreak, (2) financial assistance received, (3) the status of using maternal health services, (4) the assistance of the PHM and (5) the assistance of household members/neighbours (online supplemental file 1).…”
Section: Methodsmentioning
confidence: 99%
“…A considerable number of participants were not contactable through a given contact number. This issue was identified at the later stages of follow-up of the cohort as well amidst the COVID-19 pandemic as an obstacle to research using telephones 22…”
Section: Approachmentioning
confidence: 99%